Trend inflation in Sweden - Pär Österholm; Aubrey Poon (Örebro University School of Business, 2022)
In this paper, we estimate trend inflation in Sweden using an unobserved components stochastic volatility model. Using data from 1995Q4 to 2021Q4 and Bayesian estimation methods, we find that trend inflation has been well-anchored during the period - although in general at a level below the inflation target - and it does not appear to have been affected much by the recent high inflation numbers.
Keywords: C11; C32; C52; E32; 330; Unobserved components model; Inflation target; Bayesian estimation